Mainstreaming indigenous and local communities’ connections with nature for policy decision-making - Kamaljit K. Sangha; Jeremy Russell-Smith; Robert Costanza (Global Ecology and Conservation, 2019)
Exclusion of Indigenous and local communities' connections to the rest-of-nature is a typical problem in policy-decision making. This paper highlights the key attributes of these connections and suggests evaluation pathways to mainstream them into policy development. For this, we integrate and apply the ecosystem services (ES) and human capability concepts. Five socio-cultural and economic values relating to peoples' well-being are identified as the core attributes for developing policy tools: (1) livelihoods; (2) social values; (3) cultural values; (4) spiritual values; and (5) capabilities. For policy tools, common ES frameworks and the relevant ES evaluation techniques that can be applied along with community participatory approaches, are considered. We recommend that developing a pluralistic policy platform is essential to appropriately comprehend Indigenous and local communities' connections with nature for enhancing well-being, not just sustaining livelihoods. A three-step process: (1) identifying attributes of natural systems that are vital for peoples' well-being (beyond their livelihoods); (2) developing locally-specific integrated frameworks; and (3) evaluating identified attributes (monetary and non-monetary), is clearly described in this paper to inform the policy-makers. Recognition and understanding of Indigenous and local communities’ values for nature beyond livelihood opportunities is essential for informing inclusive sustainable development processes and policies. Keywords: Ecosystem services, Indigenous and local communities, Policy decision-making, Ecosystem services valuation, Ecosystem services framework, Well-being